Pérdida de azúcar por daño de Diatraea saccharalis Fabricius y hongos patógenos en caña de azúcar, variedades H 32-8560 y Mex 73-523, Casa Grande, La Libertad, 2014. - Uceda Villacorta, Lizeth del Pilar (2015)
In this research was determined sugar loss by damage of Diatraea saccharalis in sugarcane, varieties H 32-8560 and Mex 73-523, in Casa Grande S.A.A company, through sampling of field with mature cane nearby to harvesting. 10 fields was evaluated per variety with six barracks per field, where a strain of 10-12 stems was obtained. In infested stems was quantified drilled intemodes and healthy to determine the percentage of intensity of infestation, at the same time they were separated in healthy parts and scuttled. The total loss of recoverable sugar estimated in the evaluated area was H32-8560 102, 96 tonnes, while for Mex 73-523 was 64, 65 tons. Likewise, the loss of recoverable sugar for each 1% of I.I was 0.04 and 0.05 for H32-8560 and Mex73-523 respectively. For purposes of practical estimates a loss factor of 0.0101 t / ha in H32-8560 and 73-523 Mex 0.0092 for every 1% intensity of infestation was determined. Keywords: sugar losses, sugarcane, Diatraea saccharalis, varieties: H32-8560 and Mex 73-523.